A dual-site doping strategy for developing efficient perovskite oxide electrocatalysts towards oxygen evolution reaction. (August 2022) - Liu, Yifan; Ye, Caichao; Zhao, Shu-Na; Wu, Yunyan; Liu, Chao; Huang, Jiangfeng; Xue, Liang; Sun, Jingwen; Zhang, Wenqing; Wang, Xin; Xiong, Pan; Zhu, Junwu
Abstract: Perovskite-type ABO3 transition metal oxides are promising electrocatalysts for oxygen evolution reaction (OER), but still suffer from insufficient activities. Traditional efforts are mainly based on a single-site doping of heteroatom ions into either B-sites or O-sites of the ABO3 structures. Here we propose a dual-site doping strategy by simultaneous incorporation of iodine cations and anions into the B-sites and O-sites of ABO3 perovskite oxides, respectively. Consequently, both activated B-site transition metals with optimal eg orbital occupancy and large amount of active oxygen species were achieved for remarkably improved OER activities. Using this approach, significantly improved OER activities are achieved in some representative perovskite oxides, including Ba0.5 Sr0.5 (Co0.8 Fe0.2 )0.9 O3–δ (BSCF), SrCo0.9 O3−δ (SCO) and SrNi0.9 O3−δ (SNO). Specifically, the iodine dual-site doped BSCF boosts a small overpotential of 290 mV at 10 mA cm −2 and a small Tafel slope of 53 mV dec −1, which is about 130 mV and almost half times lower than that of pristine BSCF, respectively. Besides, this general dual-site doping strategy can also realize scale-up synthesis and achieve a gram-scale production. Our findings show a unique doping strategy to design efficient perovskite oxide electrocatalysts beyond the conventional approaches. Graphical abstract: ga1 Highlights: A dual-site doping strategy is developed for efficient perovskite oxide catalysts. Iodine cations and anions are doped into B- and O-site of ABO3 structures, respectively. Dual-site doped BSCF exhibits enhanced catalytic activities for OER than pristine BSCF. Both optimized orbital occupancy and increased active oxygen species were achieved.